Smart Metering Design and Applications - Weranga, K.S.K.; Kumarawadu, Sisil; Chandima, D. P.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
Taking into account the present day trends and the requirements, this Brief focuses on smart metering of electricity for next generation energy efficiency and conservation. The contents include discussions on the smart metering concepts and existing technologies and systems as well as design and implementation of smart metering schemes together with detailed examples.
Smart Grid and Smart Metering -- Evolution of Electricity Meters -- Basic Functionalities inside an Energy Measurement Chip -- Smart Meter Prototype Design -- Short-Term Demand Forecasting and Warning Signal Generation -- Smart Metering Applications.
Keywords: Engineering economy; Energy; Energy Efficiency (incl. Buildings).; Energy Policy, Economics and Management; Energy Systems; Energy Storage; Engineering Economics, Organization, Logistics, Marketing; Mathematical Applications in the Physical Sciences